Mosses Diversity of Tumpak Sewu Waterfall, Lumajang, East Java - Al Fajri, M Tajudin; Romaidi, Romaidi (El-Hayah : Jurnal Biologi, 2018)
Mosses or bryophytes, belonging to the lower plants, can grow on higher plants (as epiphyte), stone (epilytic), bark (corticolus), and the surface of the soil. One of the important places in East Java and having a variety of potential mosses is Tumpak Sewu Waterfall. In this place, moss grows well because of the condition of the nature, humidity, and abundant air. This study aimed to identify and calculate the population of mosses at Tumpak Sewu Waterfall, Lumajang, East Java. The research sampling has been performed along hiking trip, riverside and tourist area of Tumpak Sewu Waterfall. Quadratic method with grid lines with a plot size of 1x1 mÂ² on the right and left sides of the river was used to collect and calculate mosses population. Mosses identification was performed using mosses identification key. The population data obtained from this study were analyzed by calculating Frequency, Dominancy and Important Value Index (IVI). This study found 7 species of mosses in which 3 species belong to Family Marcahntiaceae, 2 species belongs to Bryaceae and 1 species belongs to Pottiaceae and Anthocerotaceae, respectively. The highest of IVI value is specimen K2, corresponds to Pohlia flexuosa W.J. Hooker, with 78.178%, and the lowest of IVI value is specimen K6, corresponds to Marchantia sp. with 4.524%. It can be concluded that Tumpak Sewu Waterfall has diversity for mosses that could be useful to conserve Indonesian natural resources especially lower plants.